The Effect of Keyboard Key Spacing on Typing Speed, Error, Usability, and Biomechanics: Part 1. (June 2013) - Pereira, Anna; Lee, David L.; Sadeeshkumar, Harini; Laroche, Charles; Odell, Dan; Rempel, David
Objective: In this study, we evaluated the effects of key spacing on a conventional computer keyboard on typing speed, percentage error, usability, and forearm muscle activity and wrist posture. Background: International standards that specify the spacing between keys on a keyboard have been guided primarily by design convention because few studies have evaluated the effects of key spacing on productivity, usability, and biomechanical factors. Method: Experienced male typists ( N = 37) with large fingers (middle finger length ≥ 8.7 cm or finger breadth of ≥ 2.3 cm) typed on five keyboards that differed only in horizontal and vertical key spacing (19 × 19 mm, 18 × 19 mm, 17 × 19 mm, 16 × 19 mm, and 17 × 17 mm) while typing speed, percentage error, fatigue, preference, extensor carpi ulnaris and flexor carpi ulnaris muscle activity, and wrist extension and ulnar deviation were recorded. Results: Productivity and usability ratings were significantly worse for the keyboard with spacing of 16 × 19 mm compared with the other keyboards. Differences on these measures between the other keyboards were not significant. Muscle activity tended to increase in the left forearm and decrease in the right with decreasing horizontal key spacing. There was also a trend for left wrist extension to increase and left ulnar deviation to decrease with decreasing horizontal key spacing. Reducing vertical key spacing from 19 to 17 mm had no significant effect on productivity or usability ratings. Conclusions: The study findings support key spacing on a computer keyboard between 17 and 19 mm in both vertical and horizontal directions. Applications: These findings may influence keyboard standards and the design of keyboards.